PERKEMBANGAN TRADISI PEMBUATAN GERABAH ABAR SENTANI [The Development of Abar Pottery] - Maryone, Rini (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2017)
The knowledge of making pottery in Abar Village has been around since time immemorial. Until now Abar pottery development has undergone many changes. Artisan pottery in Abar Village is determined to continue to improve the quality of production in order to compete in the market. Based on this the authors feel interested to examine more about the development of pottery tradition in Abar Village. The purpose of this research is to know the development of shape, type, function and meaning of pottery Abar. The research method is qualitative, while for the strategy in the data collection phase is literature study, observation and interview. The results: found types of pottery Abar is ebe hele (crock), sempe (belanga) and kenda / plate, and pottery that has undergone changes namely: flower pots, wall hangings, drums, table chairs, stoves. Abar pottery has three functions: function as a kitchen tool, social function and religious function.  ABSTRAKPengetahuan pembuatan gerabah di Kampung Abar sudah ada sejak dahulu kala. Hingga saat ini perkembangan gerabah Abar sudah mengalami banyak perubahan. Pengrajin gerabah di Kampung Abar bertekad untuk terus meningkatkan kualitas produksi agar mampu bersaing di pasaran. Berdasarkan hal tersebut penulis merasa tertarik untuk mengkaji lebih jauh mengenai perkembangan tradisi gerabah di Kampung Abar. Tujuan penelitian adalah untuk mengetahui perkembangan bentuk, jenis, fungsi dan makna gerabah Abar. Metode penelitian bersifat kualitatif, sedangkan untuk strategi dalam tahap pengumpulan data adalah studi pustaka, observasi dan wawancara. Adapun hasil: ditemukan jenis-jenis gerabah Abar berupa ebe hele (tempayan), sempe (belanga) dan kenda/ piring, serta gerabah yang sudah mengalami perubahan yaitu: pot bunga, hiasan dinding, tifa, kursi meja, kompor. Gerabah Abar memiliki tiga fungsi yaitu: fungsi sebagai alat dapur, fungsi sosial dan fungsi religius.